Implants coating strategies for antibacterial treatment in fracture and defect models: a systematic review of animal studies - Li, Baoqi; Thebault, Pascal; Labat, Béatrice; Ladam, Guy; Alt, Volker; Rupp, Markus; Brochhausen, Christoph; Jantsch, Jonathan Antti Michael; Ip, Margaret; Zhang, Ning; Cheung, Wing-Hoi; Leung, Shui Yee Sharon; et al. (Journal of orthopaedic translation, 2024)
Objective - Fracture-related infection (FRI) remains a major concern in orthopaedic trauma. Functionalizing implants with antibacterial coatings are a promising strategy in mitigating FRI. Numerous implant coatings have been reported but the preventive and therapeutic effects vary. This systematic review aimed to provide a comprehensive overview of current implant coating strategies to prevent and treat FRI in animal fracture and bone defect models. - Methods - A literature search was performed in three databases: PubMed, Web of Science and Embase, with predetermined keywords and criteria up to 28 February 2023. Preclinical studies on implant coatings in animal fracture or defect models that assessed antibacterial and bone healing effects were included. - Results - A total of 14 studies were included in this systematic review, seven of which used fracture models and seven used defect models. Passive coatings with bacteria adhesion resistance were investigated in two studies. Active coatings with bactericidal effects were investigated in 12 studies, four of which used metal ions including Ag+ and Cu2+; five studies used antibiotics including chlorhexidine, tigecycline, vancomycin, and gentamicin sulfate; and the other three studies used natural antibacterial materials including chitosan, antimicrobial peptides, and lysostaphin. Overall, these implant coatings exhibited promising efficacy in antibacterial effects and bone formation. - Conclusion - Antibacterial coating strategies reduced bacterial infections in animal models and favored bone healing in vivo. Future studies of implant coatings should focus on optimal biocompatibility, antibacterial effects against multi-drug resistant bacteria and polymicrobial infections, and osseointegration and osteogenesis promotion especially in osteoporotic bone by constructing multi-functional coatings for FRI therapy. - The translational potential of this paper - The clinical treatment of FRI is complex and challenging. This review summarizes novel orthopaedic implant coating strategies applied to FRI in preclinical studies, and offers a perspective on the future development of orthopaedic implant coatings, which can potentially contribute to alternative strategies in clinical practice.
Online veröffentlicht: 8. März 2024
Gesehen am 19.08.2024